Is Nationalism Really That Bad? The Case of Croatia - Matić, Davorka (Array, 2007)
Article is an investigation into the nature of nationalism and its different manifestion. It calls for analyzing nationalism issues on equal terms with other doctrines, from liberalism to communism. The article argues that nationalism is an important basis for a community's struggle towards the establishment of democracy and points to the findings in historical analyses of nation- builsin processes, where the fusion of civic and ethnic nationalism is part of every national identity, inlcuding Croatian.